Green manuring for sustainable soil fertility management and crop production (Bangla) - Ahmed, Sharif; Miajy, Abu Abdullah; Manik, Md. Zannatul Ferdous (International Rice Research Institute, 2025)
This knowledge product emphasizes the importance of green manuring as an eco-friendly and sustainable method for managing soil fertility and enhancing crop production in Bangladesh. Green manuring involves the cultivation of specific cover crops that are then incorporated into the soil to improve its organic matter, nutrient content, and overall health. This practice offers numerous benefits, including increased soil fertility, reduced reliance on chemical fertilizers, improved soil structure, and greater microbial activity, all contributing to higher and more sustainable crop yields. Additionally, green manuring helps address environmental issues such as soil erosion and nutrient runoff, promoting sustainable land use. The product provides practical guidelines for farmers, extension workers, and policymakers on selecting suitable green manure crops, as well as advice on timing and management practices tailored to local conditions. By promoting the widespread adoption of green manuring, we can significantly enhance crop productivity, ensure soil health, and support climate-resilient farming systems. Encouraging the use of green manures aligns with Bangladesh’s goals for sustainable agriculture and environmental conservation. Ultimately, this approach contributes to food security and the long-term sustainability of the country's agricultural sector. The goal of this knowledge product is to facilitate the broader dissemination and implementation of green manuring practices across diverse farming systems in Bangladesh.